Detection of Unusual Activites at ATM Using Machine Learning - D, Tejas; K, Varshini; U, Sushmitha; VK, Sunandha (International Journal of Computer Sciences and Engineering, 2025)
The idea of designing and implementation of security against ATM theft is born with the observation of our real life incidents happening around us. This project deals with prevention of ATM crimes and hence overcome the drawback found in existing technology in our society. This paper uses machine learning to enhance the security in ATM. When any suspicious activities such as a man holding a gun in his hand is detected using ORB algorithm, a person attempting to close the camera at ATM, more than two persons entering into ATM, fighting scenes happening at ATM will be detected as an unusual activity and alarm is raised at ATM and a message is passed to nearest police station. Parallelly an email consisting a snap of unusual activity will be sent to the registered police official e-mail id, this helps the police officers to analyze the situation and overcome the fake alarms.